TINGKAT KECEMASAN IBU MENJELANG PERSALINAN BERDASARKAN PENDAMPING PERSALINAN - Atun Wigati; Indah Puspitasari; Ummi Kulsum; Dwi Astuti (Universitas Muhammadiyah Kudus, 2023)
factors that influence childbirth or what is often called the 5P (Passage, Power, Passenger, Psychology, Helper). Having a companion during childbirth helps mothers reduce mortality, because pregnancy and childbirth are sad events that can be prevented and should not happen. The purpose of this study was to examine the relationship between the anxiety level of mothers in childbirth and birth attendants at BPM Farikha Prambanan Kudus. Research Methods, this type of correlation analysis research uses a cross-sectional time approach, a sample is determined from the population with a sample selection technique using Total Sampling, namely 33 respondents are obtained. computerized assistance and statistically tested using the Kendal Tau test. Research Results Most of the childbirth assistance was assisted in stage 1 by 16 people (39.4%). The condition of the mother's anxiety before delivery is mostly moderate anxiety as many as 12 people (36.4%). Conclusion There is a relationship between birth attendants and maternal anxiety about labor at BPM Farikha Prambata Kudus. It can be seen from Kendall's tau arithmetic test (0.453) Kendall's tau table (0.344) n: 33 and p value 0.004 0.05.